NMgO-incorporated PLLA bone scaffolds: Enhanced crystallinity and neutralized acidic products. (15th July 2019) - Shuai, Cijun; Zan, Jun; Qi, Fangwei; Wang, Guoyong; Liu, Zheng; Yang, Youwen; Peng, Shuping
Abstract: Poly‑l‑lactic acid (PLLA) is a promising bone repair material because of its good biocompatibility and natural degradability. Nevertheless, the poor mechanical properties and local inflammatory response limits its further application in bone repair. In this research, nano magnesium oxide (nMgO) was incorporated into PLLA scaffold manufactured by selective laser sintering technique. Results shown that nMgO with good affinity to PLLA could act as nucleating agent during crystallization process and effectively enhance the crystallinity of PLLA, which was proved by the isothermal behavior and non-isothermal behavior analysis. The evolution of crystallization was also achieved by polarized optical microscopy. Mechanical tests confirmed that the tensile strength, young modulus and Vickers hardness of PLLA/3nMgO was enhanced by 38%, 24% and 11%, respectively, as compared with PLLA. On the other hand, the incorporated nMgO neutralized the acid degradation by-products of PLLA, forming a weak alkaline environment which might contribute to avoiding sever local inflammation after implantation. Moreover, in vitro cell culture revealed an improved biocompatibility of PLLA/nMgO scaffolds. All these positive results suggested that PLLA/3nMgO scaffold was a potential material for bone repair application. Graphical abstract: Unlabelled Image Highlights: Porous scaffold is successfully fabricated via selective laser sintering. The crystallinity of PLLA scaffold is enhanced after the incorporation of nMgO. The acid degradation by-products of PLLA are neutralized by nMgO. The mechanical properties and biocompatibility are improved simultaneously.